Pelaksanaan Metode Drill pada Kegiatan Pengembangan Diri Paduan Suara di SMP Adabiah Padang - Aisiah Thasya; Irdhan Epria Darma Putra (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This study aims to describe the implementation of the drill method in choir self-development activities at SMP Adabiah Padang. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery and kemera. Data collection techniques are carried out by observation, interviews and documentation. The steps of analyzing data are data collection, data reduction, data display and data verification. The results showed that vocalizing, articulation and intonation techniques in singing with the application of the drill method can improve skills in choir self-development activities. Vocalizing techniques with the application of the drill method can provide flexibility to the vocal cords when singing, with the aim that when singing the vocal cords are not surprised and some organs that play a role when singing such as the mouth, throat of the tongue become more flexible so light exercise is needed. Articulation techniques after vocal warm-up are practiced repeatedly on Mars Adabiah Padang songs so that students can master Mars Adabiah Padang song singing techniques with good articulation. Exercises with intonation techniques that students do repeatedly in the song Mars Adabiah Padang can be done quite well. This was proven during the final presentation, namely singing the song Mars Adabiah Padang" using the right and appropriate intonation.